ANALISIS PREFERENSI KONSUMEN TERHADAP BUAH SALAK (Salacca edulis) DI PASAR TRADISIONAL KOTA YOGYAKARTA - Reza Rori; Ari Astuti (Fakultas Pertanian UST, 2018)
This study aims to examine the attributes of the fruits becaming consumer preferences and the most considered of attributes by consumers in the decision to buy fruits in the traditional market of Yogyakarta City. The basic method in this research is descriptive method, and its implementation by survey technique. The research location using three traditional markets chosen purposively. Determination of the sample is done by quota sampling method with the number of respondents 30 people. The type of data used is primary data and secondary data. The analysis used is chi square analysis and analysis of Fishbein multiattribute attitude. The result of chi square analysis showed that all variables of fruits were significantly different at 95% confidence level. That is, the attributes of the fruits effect on consumer preferences in the traditional market of Yogyakarta. Salak fruit is a consumer preference in the traditional market of Yogyakarta City is the fruit of bark that has attributes; sweet taste, medium size, texture of fine meat, and blackish brown skin color. Based on Fishbein analysis it is known that most attributes considered by consumers in purchasing decisions of fruits are flavor attributes. The most attribute sequences considered in the least-considered are fruit flavors, fruit size, fruit pulp texture, and fruit skin color.